2021
DOI: 10.22146/ijc.63573
|View full text |Cite
|
Sign up to set email alerts
|

A Green Method for Synthesis of Silver-Nanoparticles-Diatomite (AgNPs-D) Composite from Pineapple (<i>Ananas comosus</i>) Leaf Extract

Abstract: This study aims to develop a green method to load silver nanoparticles (AgNPs) into the diatomite (D) pores to produce AgNPs-D composite material. The AgNPs were synthesized by pineapple leaf extract at the temperature of 70 °C for 30 min. The composite formation was characterized by UV-Vis, FTIR, TGA, particle sizes analysis, gravimetric, and color observation. The appearance of surface plasmon bands in 440–460 nm confirms the AgNPs formation. The percentage of the AgNO3 which converted to AgNPs was 99.8%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…The current study corresponds to the study of [22], where the results of the FTIR analysis of the aqueous solution of pineapple leaves and AgNPs synthesized by pineapple leaves showed that natural substances such as sugars (sucrose, glucose) are responsible for the biosynthetic reduction of Ag + and the formation of AgNPs. This also corresponds to the study of [23], where the results of the FTIR showed the presence of hydroxyl, carbonyl, and carboxyl groups of the main compounds present in pineapple leaf extract, and these groups are responsible for the Ag + reduction and stability of the AgNPs synthesized. Moreover, a study by [24] found that plant-based proteolytic enzymes can be used as agents for the reduction and stability of metal ions for the synthesis of nanoparticles by synthesizing gold nanoparticles using the bromelain enzyme.…”
Section: Ftir Analysis Of Bromelainsupporting
confidence: 84%
“…The current study corresponds to the study of [22], where the results of the FTIR analysis of the aqueous solution of pineapple leaves and AgNPs synthesized by pineapple leaves showed that natural substances such as sugars (sucrose, glucose) are responsible for the biosynthetic reduction of Ag + and the formation of AgNPs. This also corresponds to the study of [23], where the results of the FTIR showed the presence of hydroxyl, carbonyl, and carboxyl groups of the main compounds present in pineapple leaf extract, and these groups are responsible for the Ag + reduction and stability of the AgNPs synthesized. Moreover, a study by [24] found that plant-based proteolytic enzymes can be used as agents for the reduction and stability of metal ions for the synthesis of nanoparticles by synthesizing gold nanoparticles using the bromelain enzyme.…”
Section: Ftir Analysis Of Bromelainsupporting
confidence: 84%